ROTATIONAL BARRIERS OF 1,1'-BINAPHTHYLS - A COMPUTATIONAL STUDY - Clark, Timothy; Schleyer, Paul; et al. (Journal of Organic Chemistry, 1993)
The activation energies for rotation about the sigma-bonds of 1,1'-binaphthyl (1) and 2,2'-dibromo-l,l'-binaphthyl (2) have been computed with MNDO, AM1, and PM3 and of 2,2'-dilithio-l,l'-binaphthyl (3).2EDA (ethylenediamine) (3a) with MNDO. All methods find that 1 should racemize preferably through the anti path, in agreement with previous force field calculations. The PM3 rotational barrier for 1 (23.1 kcal/mol) matches the experimental value (22.5 kcal/mol) best; the ground-state bond lengths correspond well with the X-ray data. We developed a procedure which evaluates the distortion and the steric repulsion effects in the transition structures roughly. In 1, distortion effects (e.g., ring deformation) account for about 2/3 of the activation energy. On the basis of the rotational behavior of 1, previous authors have only considered the anti racemization mechanism to be viable for 2,2'-dimethyl-l,l'-binaphthyl (4). In contrast, we found that in 2 (methyl is about the same size as bromine) the syn pathway is favored substantially over the anti route by 15.1 (MNDO), 20.6 (AM1), and 26.3 (PM3) kcal/mol. For 2, PM3 again yields the lowest rotational barrier (30.3 kcal/mol) but the AM1 value (38.4 kcal/mol) is in better agreement with an earlier estimate for 4 (37-40 kcal/mol). The transition structures (TS) related to 2 are even more strongly dominated (75-93 %) by distortion effects than those for l. Two energetically almost degenerate energy minima are computed with MNDO for 3a: one with the lithiums symmetrically doubly bridging the markedly twisted naphthyl rings (twist angle: 42.5-degrees) and the other with each lithium closely coordinated to the contiguous pi-system (twist angle: 122.0-degrees). Despite the size of the Li.ethylenediamine 2,2'-substituents in 3a, the anti racemization pathway is preferred by 6.4 kcal/mol with an unusually close Li ... H contact (1.79 angstrom). However, the syn-TS is 6.3 kcal/mol lower in energy with Li.EDA (3a) instead of hydrogens (1) in the 2,2'-positions. Thus, the syn-TS of 3a profits from electrostatic stabilization through lithium double bridging. Upon further rotation, the lithium atoms swap their counterions. To correct for the known overestimation of the Li-C bond strength by MNDO, we compared its performance on a model system (1,4-dilithio-1,3-butadiene (6)) with the MP2/6-31G*//6-31G* results. Deviations between the semiempirical and the ab initio geometries of four isomers of 6 suggest that the magnitude of the MNDO overestimation are 8 kcal/mol for Li-C and 4 kcal/mol for Li-H interactions. When these corrections are applied, the activation energy of 3a (anti-TS: 22.1 kcal/mol) should be close to the experimental estimate for 2,2'-dilithio-l,l'-binaphthyl (3) in solution (18.4 kcal/mol).